Assessment of Bachelor of Technology in Biomedical Communications Degree Curriculum - Metta, Chongchareon; Kuhirunyaratn, Piyathida; Musikapodoke, Dusadee; Kheonkaew, Banjong (Srinagarind Medical Journal, 2013)
Background: Assessment the curriculum is one of the essential factor in education to use the results as a feedback data to manage the education efficiently in accordance with the need of society-- in line with medical education quality assurance. Objectives: To assess the curriculum of the Bachelor of Technology Program in Biomedical Communications as perceived by the students graduating in 2005. Subject and Method: This was descriptive research using both concurrent and analytical evaluations. Seventeen of 2nd-year students were surveyed on February 2006. The checklist and the 1-5 Likert’s scale questionnaire were used and developed some categories as research instrument. The collected data were analyzed by using SPSS V.11.5 and the results were presented as percentages, means and standard deviation. Result:The response rate was 100% (males 76.5%, females 23.5%) whose GPAs ranged between 2.00-2.49 (5.9%), 2.50 - 2.99 (76.5%) and 3.00 - 3.49 (17.6%). Most students in the 1st year were more satisfied and in the 2nd year satisfied with the instruction and the curriculum content (3.73±0.61, 3.37±0.62 respectively). The study revealed that most students were satisfied with the program’s arrangement in the general education and more satisfied with specific subject and free elective (3.34±0.70, 4.08±0.53 and 3.97±0.71 respectively). Courses that the students found inappropriate was biostatistics (2.47±1.23) Conclusion: Overall the students were satisfied with the instruction and curriculum in the general education, specific subjects and free elective. One subject in the general education was considered inappropriate. An effort should be made, therefore, to make these courses more useful to students of this level. Finally, the students felt positive about the opportunities to be biomedical communications specialists. Key word: Assessment, curriculum, biomedical communications students, Likert’s scale.